2016
DOI: 10.1186/s40621-016-0096-1
|View full text |Cite
|
Sign up to set email alerts
|

The effects of roadway characteristics on farm equipment crashes: a geographic information systems approach

Abstract: BackgroundTractors and other slow-moving self-propelled farm equipment are often used on public roadway to transfer goods from the farm to a market or distributer. Increased roadway exposure has led to a growing concern on the occurrence of farm equipment crashes. This study aims to compare characteristics of road segments with farm equipment crashes to road segments without farm equipment crashes in the state of Iowa.MethodsData were obtained from the Iowa Department of Transportation from 2005 to 2011 on all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 13 publications
(32 reference statements)
0
18
0
2
Order By: Relevance
“…Low speed of displacement in relation to the other vehicles on the road Correa et al, 2005;Peek-Wing et al, 2007;Costello, Schulman, & Mitchell, 2009;Reis & Machado, 2009;Gkritza et al, 2010;Pinzke et al, 2012;Burin & Bezerra, 2013;Dimitrovski et al, 2013;Santos Monteiro & Macedo, 2013;Greenan et al, 2016;Tuure, Latti, & Kaila, 2016 Greater dimensions, often wider than a traffic lane, also invading the road shoulder Costello, Schulman, & Mitchell, 2009;Gkritza et al, 2010;Burin & Bezerra, 2013;Santos Monteiro, & Macedo 2013;Greenan et al, 2016 Nonstandard lighting and/or signaling, deficient or missing Correa et al, 2005;Reis & Machado, 2009;Gkritza et al, 2010;Burin & Bezerra, 2013;Tuure, Latti, & Kaila, 2016;CEMA, 2017 Often carries passengers on the fenders Reis & Machado, 2009;Santos, Monteiro, & Macedo, 2013 Usage lifespan, in some cases of more than 20 years, which implies on the absence of safety equipment, such as: a) rollover protective structure; b) seat belt; c) mirrors. Correa et al, 2005;Reis & Machado, 2009;Gkritza et al, 2010;Pinzke et al, 2012;Montemor, Veloso, & Areosa, 2015;CEMA, 2017 Figure 1.…”
Section: Characteristic Authorsmentioning
confidence: 99%
See 3 more Smart Citations
“…Low speed of displacement in relation to the other vehicles on the road Correa et al, 2005;Peek-Wing et al, 2007;Costello, Schulman, & Mitchell, 2009;Reis & Machado, 2009;Gkritza et al, 2010;Pinzke et al, 2012;Burin & Bezerra, 2013;Dimitrovski et al, 2013;Santos Monteiro & Macedo, 2013;Greenan et al, 2016;Tuure, Latti, & Kaila, 2016 Greater dimensions, often wider than a traffic lane, also invading the road shoulder Costello, Schulman, & Mitchell, 2009;Gkritza et al, 2010;Burin & Bezerra, 2013;Santos Monteiro, & Macedo 2013;Greenan et al, 2016 Nonstandard lighting and/or signaling, deficient or missing Correa et al, 2005;Reis & Machado, 2009;Gkritza et al, 2010;Burin & Bezerra, 2013;Tuure, Latti, & Kaila, 2016;CEMA, 2017 Often carries passengers on the fenders Reis & Machado, 2009;Santos, Monteiro, & Macedo, 2013 Usage lifespan, in some cases of more than 20 years, which implies on the absence of safety equipment, such as: a) rollover protective structure; b) seat belt; c) mirrors. Correa et al, 2005;Reis & Machado, 2009;Gkritza et al, 2010;Pinzke et al, 2012;Montemor, Veloso, & Areosa, 2015;CEMA, 2017 Figure 1.…”
Section: Characteristic Authorsmentioning
confidence: 99%
“…The data released by the National Department of Infrastructure and Transport (DNIT, 2014) show that Brazil has 1.71 million kilometers of roads, being 7% federal roads, 15% state roads and 78% municipal roads In addition to the increased volume and density of vehicles in traffic, high speed limits, type and width of the road lanes are factors associated with the occurrence of accidents with farm machinery on public roads (Greenan et al, 2016). Studies by Costello, Schulman, andMitchell (2009), Harland et al (2014), and Greenan et al (2016) showed that the addition of vehicle density in traffic strongly contributes to the occurrence of accidents, increasing the risk of collisions with farm equipment.…”
Section: Accidents With Tractors On Public Roadsmentioning
confidence: 99%
See 2 more Smart Citations
“…A queda nas vendas de tratores entre os anos de 1990 e 2006 foi compensada pela elevação da potência das máquinas comercializadas, com aumento da representatividade de tratores na faixa de 100 (73,5 kW) a 199 cv (146,4 kW) [24]. Além do aumento no volume e na densidade do tráfego de veículos, os limites de velocidade altos, o tipo e a largura da via são fatores associados à ocorrência de acidentes com máquinas agrícolas em vias públicas [25]. Estudos realizados por Harland; Greenan; Rramirez.…”
Section: Densidade Do Tráfego De Veículos (Número De Veículos Por Quiunclassified